Evaluation of Immunomodulatory Activity of Milk-Based Nutraceutical Formulations Containing Alcoholic Extracts of Nyctanthes arbor-tristis, Asparagus racemosus, Withania somnifera, Berberis aristata, and Zingiber officinale in Mice - Chavan, Leena; Gadgoli, Chhaya (Journal of Neonatal Surgery, 2025)
This study investigates the immunomodulatory potential of three milk-based nutraceutical formulations containing extracts from Nyctanthes arbor-tristis, Zingiber officinale, and Withania somnifera (F1), Nyctanthes arbor-tristis, Zingiber officinale, and Asparagus racemosus (F2), and Nyctanthes arbor-tristis, Zingiber officinale, and Berberis aristata (F3) in comparison to the standard immunosuppressant drug, cyclophosphamide. The formulations were developed using a spray drying technique to improve the stability, absorption, and delivery of the active plant constituents. This approach is intended to enhance the shelf life and ensure the product can be used conveniently at any time, without compromising its efficacy. These formulations were evaluated for immunomodulatory activity cyclophosphamide-induced myelosuppression in mice. Our findings demonstrated a marked enhancement in immune responses in groups treated with each of the individual formulations compared to the control group, the standard treatment group (negative control), and the group treated with a combination of the formulation and cyclophosphamide. These results suggest that the plant extract-loaded nanoparticles within the milk-based formulations hold promising potential as effective immunomodulatory agents.